Antihypertensive treatment and risk factors for syncope in asymptomatic aortic stenosis patients with hypertension. (17th February 2022) - Wu, Meihua; Gu, Ping; Cao, Qianqiang; Gong, Aibin; Tan, Wenliang; Hong, Dezhi
ABSTRACT: Background: Evidence for treating hypertension in patients with asymptomatic aortic valve stenosis(AS) is scarce. Objectives: Given the paucity of data on the relationship between syncope and antihypertensive treatment in aortic stenosis. This study sought to investigate this association in patients admitted to our hospital. Methods: A total of 158 patients with asymptomatic moderate or severe aortic stenosis were analyzed. Follow-up was conducted by clinic visit, telephone contact, or review of electronic medical records. Outcomes were syncope. Results: Hypertension were documented in 90 of the 158 patients with moderate or severe AS, and 77 of them received antihypertensive medications. During an average 28 months follow-up period, the occurrence of syncope was observed in 13 patients. Among them, 8 were in antihypertensive group (n = 77) and 5 in normotensive group (n = 68). There was no significant difference in incidence of syncope between the two groups. Patients with treated hypertension and syncope had a lower stroke volume index (SVi), a higher valve arterial impedance (ZVA ), a smaller SAC than those without. Kaplan-Meier analysis showed that there was no significant difference in syncope cumulative incidence between antihypertensive group and normotensive group (log rank P = .478). Multivariate cox regression analysis showed that both ZVA (hazard ratio:19.006, 95% confidence interval: 4.664 to77.448; P = .002) and LVMI (hazard ratio:1.484, 95% confidence interval: 1.427 to 5.157; P = .016) were associated with development of syncope, whereas hypertension were not related independently to syncope (hazard ratio:0.935, 95% confidence interval: 0.786 to3.173; P = .869). Conclusions: In patients with moderate or severe AS, concomitant hypertension, and antihypertensive treatment didn't increase the occurrence of syncope, whereas higher ZVA was independently associated with greater risk of syncope.